Prevalensi Status Bekerja Pemuda Fresh Graduate di Indonesia: Analisis Data Sakernas - Natalia, Christiayu; Febri Putranto, FX Gugus (Seminar Nasional Official Statistics, 2024)
School to work transition is a crucial phase for individual success in the labor market. However, this transition is not occurring smoothly for fresh graduates in Indonesia. Despite stable economy in 2022, labor market absorption rate for fresh graduates in Indonesia remains low. This phenomenon is important as it is related to achieving Indonesia Emas 2045 through the quality of human capital among young people. This study aims to (1)analyze the general characteristics of fresh graduates based on their employment status; and (2)analyze the effect of demographic, human capital, and regional characteristics on the employment status. The data used is the microdata from Sakernas August 2022. The results of multinomial logistic regression show that human capital characteristics increase the probability of working in the formal sector but decrease the probability of working in the informal sector compared to being unemployed. These findings indicate a wait-and-see behavior in the labor market.